Open to Debate: Reducing Polarization by Approaching Political Argument as Negotiation. Issue 3 (21st July 2021) - Iwry, Jonathan
Abstract : One of the most prominent features of political polarization is the decline in civility and quality of political discourse. Those with opposing political viewpoints often refuse to engage in dialogue, and their limited attempts often end in unproductive conflict. In this article, I examine the commonalities between political arguments and negotiations to consider how the principles of negotiation theory can usefully be applied to improve the quality of political discourse. I survey existing research on political and moral psychology to analyze the competitive dynamics and emotions underlying the use of reason in political contexts. I propose a model of political arguments in which stated positions function as proxies for personal, moral, and tribal interests, and offer specific examples of prescriptive strategies for how negotiation theory can foster constructive dialogue. My core contention is that most political arguments reflect a zero‐sum dynamic that inflames unproductive competitive instincts, whereas an interest‐based approach moves beyond political positioning to allow for more substantive reflection and mutual understanding. Effective argumentation requires parties to view rational dialogue as consistent with their mutual interests, using shared curiosity, trust in good faith, and other cooperative principles as procedural ground rules. It also requires parties to address the social and emotional dynamics influencing their shared use of reason, working to replace adversarial tension with a personal inclination toward fair‐mindedness and reciprocity.